Analisis Konsep Rancangan Produk NutriFarm Website Sebagai Inovasi Peternakan Masa Depan - Febrianti, Vira; Hilmi, Dafa Fadhilah; Nuhita, Nashifa Maisun; Raziqi, Ahmad Raziqi; Devy Dwi Arianty; Izzatu Salisah Mafatihurrohmah; Maura Y’nauri Yasmin Hidayat; Hikam Muta’aly Al Isyraq (LANCAH: Jurnal Inovasi dan Tren, 2025)
This study aims to review the latest literature on livestock nutrition, feed management, and digital technology developments in animal husbandry, and how these findings support the development of the NutriFarm Website as a web-based nutrition management platform. The results show that the main problems in livestock farming, especially on a small scale, include nutritional imbalances, high rates of metabolic diseases such as hypocalcemia due to calcium deficiency, and low literacy among farmers in feed management. On the other hand, digital technologies such as the Internet of Things (IoT), decision support systems, and feed automation have been proven to improve livestock efficiency and health, but their adoption remains low due to limited access and complexity of use. The literature synthesis confirms that simple and accessible digital platforms, such as the NutriFarm Website, have the potential to be practical solutions to help farmers calculate nutritional requirements, understand feed composition, and prevent diseases related to nutritional imbalances. This study concludes that the NutriFarm Website not only improves feed management efficiency but also strengthens farmer education and encourages the adoption of technology to support productivity and sustainability in Indonesia's livestock sector.